Basement evolution of the Sierra de la Ventana Fold Belt: New evidence for Cambrian continental rifting along the southern margin of Gondwana - Rapela, Carlos Washington; Pankhurst, R. J.; Fanning, C. M.; Grecco, Laura Edith (Journal of the Geological Society)
U-Pb sensitive high-resolution ion microprobe data together with geochemical and Nd isotope analyses obtained in the basement complex of the Sierra de la Ventana Fold Belt indicate that the Early Palaeozoic passive margin history of the basin followed Cambrian magmatism related to rifting in a 600 Ma Neoproterozoic crust. The Cambrian episode started with intrusion of 531 ± 4 and 524 ± 5 Ma A- and I-type granites derived from a dehydrated infracrustal source (cNd530 - 3.1 to -5.9), and culminated with eruption of high-Zr peralkaline spherulitic rhyolites derived from an undepleted lithospheric mantle (509 ± 5 Ma; cNd509 +0.5 to +1.0). These rift-related magmatic rocks were covered by shelf sediments deposited along a once-continuous passive margin, encompassing the Sierra de la Ventana Fold Belt, the Cape Fold Belt, the Falkland/Malvinas microplate and the Ellsworth Mountains block in Antarctica. The Cambrian rifting event defined the outline shape of the southern part of Gondwana, and can be regarded as the initiation of the supercontinent stage, which lasted until Jurassic break-up. The conjugate continental fragments separated from Gondwana during the Cambrian rifting could be the source for microcontinents with c. 1000 Ma basement rocks that collided with the proto-Andean margin during Ordovician-Silurian times. Fil: Rapela, Carlos Washington. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigaciones Geológicas. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Investigaciones Geológicas; Argentina Fil: Pankhurst, R. J. British Antartic Survey; Reino Unido. NERC Isotope Geosciences Laboratory; Reino Unido Fil: Fanning, C. M. The Australian National University; Australia Fil: Grecco, Laura Edith. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Geológico del Sur. Universidad Nacional del Sur. Departamento de Geología. ...